Creativity, Cities, and Innovation. (May 2014) - Lee, Neil; Rodríguez-Pose, Andrés
The creative industries have long been seen as an innovative sector. More recent research posits that creative occupations are also a fundamental, but overlooked, driver of innovation. Theory also suggests cities are important for both creative industries and occupations, with urban environments helping firms innovate. Yet little empirical work has considered the links between creative industries, occupations, cities, and innovation at the firm level. This paper addresses this gap using a sample of over 9000 UK SMEs. Our results stress that creative industries firms are more likely to introduce original product innovations, but not those learnt from elsewhere. Creative occupations, however, appear a more robust general driver of innovation. We find no support for the hypothesis that urban creative industries firms are particularly innovative. However, creative occupations are used in cities to introduce product innovations learnt elsewhere. The results suggest that future work needs to seriously consider the importance of occupations in empirical studies of innovation.